Conformational, crystalline and rheological properties of poly(octadecyl-co-methyl acrylate) statistically random copolymers. Issue 9 (7th February 2023) - Pan, Xuejun; Wu, Weiling; Zhu, Mo; Yang, Jixian; Yan, Zhi-Chao; Li, Lianwei
Abstract : This work reports the conformational, crystalline and rheological properties of poly(octadecyl-stat-methyl acrylate) (P(ODA x -stat-MA y ) N b ), where N b is the degree of polymerization, and x and y are the molar fraction of ODA and MA, respectively. Abstract : This work reports the conformational, crystalline and rheological properties of poly(octadecyl- stat -methyl acrylate) (P(ODA x - stat -MA y ) N b ) random copolymers, where N b is the overall degree of polymerization, and x and y represent the molar fraction of ODA and MA, respectively, with x + y = 1.0. By a combination of ATRP, esterification and graft-onto strategies, a library of P(ODA x - stat -MA y ) N b samples with statistically random distribution features have been prepared. The average molar mass ( M ), viscometric radius ( R η ) and intrinsic viscosity ([ η ]) are determined in solution, and a scaling-law of R η ∼ M 0.28 is established. For the conformation of P(ODA x - stat -MA y ) N b, it is found that [ η ] increases with x first due to chain expansion but decreases with x when x > 0.25, because the increase in segmental density dominates at high x . The rheological measurement indicates that the viscous flow activation energy remains constant first and then increases with decreasing x, reflecting the reduction of internal plasticization. In addition, the entanglement plateau modulus for the sample with x = 0.99 is one decade lower than that of the backbone, which is consistent with the prediction for the densely grafted bottlebrush polymers. This work provides a new strategy to synthesize model PODA-based random copolymers, and clarifies the change of the chain conformation, crystalline properties, and rheological behavior with the grafting density x, and this knowledge could be used to regulate the conformation and processing properties of comb/bottlebrush polymers by precisely designing the alkyl side chain's grafting density and length.